Il corpo aumentato: tra arte e tecnica. Intervista a Stelarc (Itinera, 2016)
In this interview to Cypriot artist Stelarc, the interviewee is asked questions revolving around the treatment of the body in his performances, with particular attention to the multiple meaningsthat the utterly malleablebody of the actor takes on,especially thanks to the opportunitiesafforded bydigitalisation and thenew technologies.